The difference level of depression between retired civil servant that works with its not working - Sani, Mahendra Budi Arma; , Prof.Dr.dr.H.M. Fanani Sp.Kj (K); , dr. Sri Wahyu Basuki. M.Kes (2016)
Retirement is often considered an unpleasant realities so ahead of its time comes, most people are worried because they do not know what kind of life will be encountered later. Fears for retirement, making a lot of people experiencing serious problems both in terms of mental and physical. To know and analyze the difference level of depression of retired civil servant who worked with that did not work.. This study is an observational analytic with cross sectional design. taken with total sampling method and using BDI questionaire. The statistical test used was Chi-Square test.. From the analysis of the data showed p-value= 0.000 (p <0.05), so that statiscally, it means theres is a significan difference depression level of retired civil servant that works and not working. There are differences in the level of depression among retired civil servant who does not work with Retired civil servants working.